2012
DOI: 10.1111/j.1740-8709.2012.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of market‐based community distribution of Sprinkles in western Kenya

Abstract: To evaluate the sustainability of market-based community distribution of micronutrient powders (Sprinkles ® , Hexagon Nutrition, Mumbai, India.) among pre-school children in Kenya, we conducted in August 2010 a follow-up survey, 18 months after study-related marketing and household monitoring ended. We surveyed 849 children aged 6-35 months randomly selected from 60 study villages. Nutritional biomarkers were measured by fingerstick; demographic characteristics, Sprinkles purchases and use were assessed throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…After research support ended, continued monitoring activities relied on reporting systems maintained by the implementer, rather than household‐level data. These continued activities focused on the supply and distribution of MNP and promotional materials, as well as promotional activities undertaken by distributors (Suchdev et al, 2013). Sale of subsidized MNP at small stores/kiosks and pharmacies in Tanzania had effective internal monitoring systems for tracking supply and sales when the partners were involved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After research support ended, continued monitoring activities relied on reporting systems maintained by the implementer, rather than household‐level data. These continued activities focused on the supply and distribution of MNP and promotional materials, as well as promotional activities undertaken by distributors (Suchdev et al, 2013). Sale of subsidized MNP at small stores/kiosks and pharmacies in Tanzania had effective internal monitoring systems for tracking supply and sales when the partners were involved.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of published papers report on evaluations in the context of a pilot project (Creed‐Kanashiro, Bartolini, Abad, & Arevalo, 2015; Harris et al, 2012; Jefferds et al, 2015; Korenromp et al, 2015; Loechl et al, 2009; Mirkovic, Perrine, Subedi, Mebrahtu, Dahal, & Jefferds, 2016; Mirkovic, Perrine, Subedi, Mebrahtu, Dahal, Staatz, et al, 2015; Nguyen et al, 2016; Suchdev et al, 2010, 2013; Sun et al, 2011), with the exception of Bangladesh which reports on national programmes (Afsana, Haque, Sobhan, & Shahin, 2014; Angdembe, Choudhury, Haque, & Ahmed) and three large‐scale MNP distribution in refugee camps and in emergency contexts (de Pee et al, 2007; Kodish, Rah, Kraemer, de Pee, & Gittelsohn, 2011; Rah et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…These cards serve as reminders, visual cues and motivators to use MNP, and may help to establish regular intake routines, even if the boxes are not marked after use. Motivation and demand among participants are not static, especially for long-term interventions of several months or years that are at high risk of intervention fatigue; thus, 'refreshing' the promotion materials and messages and giving ongoing reminders of the benefits and to continue practising the intervention are needed (13,14) . The literature demonstrates that factors at multiple levels influence adherence (1) , but the cross-sectional design and content of the surveys limited our ability to explore many of these potentially critical issues.…”
Section: Discussionmentioning
confidence: 99%
“…This setting is characterized by endemic malaria transmission, high rates of diarrheal diseases because of poor access to safe water, and anemia (11). Details of the study methodology, including the promotion and monitoring of the interventions and effects on primary nutrition outcomes have been published elsewhere (10, 12, 13). Formative research on cultural conceptions of morbidity has also been previously reported (14).…”
Section: Methodsmentioning
confidence: 99%